Retinal metastasis from lung adenocarcinoma: a case report - Li, Danfeng; Luo, Lifu; Yang, Bo; Xiao, Jun (Frontiers in Oncology, 2025)
Retinal metastasis is an exceedingly rare manifestation of systemic cancer, accounting for less than 1% of ocular metastases. Lung adenocarcinoma is among the primary tumors that can metastasize to the retina, though such cases are seldom reported. We present a 70-year-old male with a history of lung adenocarcinoma who presented with a decline in vision in his left eye. Fundus examination revealed a large yellow-white lesion with hemorrhage in the macula and temporal retina. Multimodal imaging, including optical coherence tomography (OCT) and fluorescein angiography (FA), confirmed the diagnosis of retinal metastasis. This case underscores the importance of considering retinal metastasis in cancer patients with visual disturbances. Early diagnosis through comprehensive ophthalmic evaluation is crucial to avoid misdiagnosis.